Potential for inhibition of checkpoint kinases 1/2 in pulmonary fibrosis and secondary pulmonary hypertension. Issue 3 (5th July 2021) - Wu, Wen-Hui; Bonnet, Sébastien; Shimauchi, Tsukasa; Toro, Victoria; Grobs, Yann; Romanet, Charlotte; Bourgeois, Alice; Vitry, Geraldine; Omura, Junichi; Tremblay, Eve; Nadeau, Valerie; Orcholski, Mark; et al.
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease characterised by exuberant tissue remodelling and associated with high unmet medical needs. Outcomes are even worse when IPF results in secondary pulmonary hypertension (PH). Importantly, exaggerated resistance to cell death, excessive proliferation and enhanced synthetic capacity are key endophenotypes of both fibroblasts and pulmonary artery smooth muscle cells, suggesting shared molecular pathways. Under persistent injury, sustained activation of the DNA damage response (DDR) is integral to the preservation of cells survival and their capacity to proliferate. Checkpoint kinases 1 and 2 (CHK1/2) are key components of the DDR. The objective of this study was to assess the role of CHK1/2 in the development and progression of IPF and IPF+PH. Methods and results: Increased expression of DNA damage markers and CHK1/2 were observed in lungs, remodelled pulmonary arteries and isolated fibroblasts from IPF patients and animal models. Blockade of CHK1/2 expression or activity-induced DNA damage overload and reverted the apoptosis-resistant and fibroproliferative phenotype of disease cells. Moreover, inhibition of CHK1/2 was sufficient to interfere with transforming growth factor beta 1-mediated fibroblast activation. Importantly, pharmacological inhibition of CHK1/2 using LY2606368 attenuated fibrosis and pulmonary vascular remodelling leading to improvement in respiratory mechanics and haemodynamic parameters in two animal models mimicking IPF and IPF+PH. Conclusion: This study identifies CHK1/2 as key regulators of lung fibrosis and provides a proof of principle for CHK1/2 inhibition as a potential novel therapeutic option for IPF and IPF+PH.